Some clinical-epidemiological, endoscopic and histological aspects in elderly with gastric cancer - Odalis Despaigne Guillot; Anely Rosalia León Columbié; Jesús Díaz Fonden; Yurislena Monier Martinez (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: Gastric cancer occupies the fifth place in incidence among all types of malignancies and is the second cause of death in the world, as most of the patients are more than 60 years when being diagnosed. Objective: To characterize aged patients according to variables of interests. Methods: An observational, descriptive and series of cases study was carried out in 56 patients older than 60 years with endoscopic and histologic diagnosis of gastric cancer, who were admitted in Saturnino Lora Teaching Provincial Clinical-Surgical Hospital, during 2016-2019. Results: Elderly in the age group 60-69 years predominated (46.4 %), mainly of the male sex (67.8 %), and the most frequent symptoms were epigastralgia (82.1 %) and the early fullness sensation (67.8 %). Among the most relevant characteristics of the tumoral lesions there were the antropiloric location (55.3 %), the ulcerated presentation in the endoscopy (51.7 %), and the histic variety mildly differentiated adenocarcinoma (43.4 %), likewise, the existence of Helicobacter pylori was confirmed in 52,5 % of the pathological biopsy results. Conclusions: It is interesting to consider the presence of a gastric adenocarcinoma in patients older than 60 years expressing gastric symptoms, mainly if they are men or suffer from epigastralgia, even more if when carrying out the esophagogastroduodenoscopy, an ulcerated lesion of antropiloric location is observed.